Clinical significance of galectin-3 expression in urinary bladder carcinoma - Jaudah Ahmed Al-Maghrabi; Mohamad Nidal Khabaz (Journal of International Medical Research, 2023)
Objective To uncover the clinical significance of galectin-3 in the evolution of urinary bladder cancer by defining galectin-3 expression and examining the relationship between its expression in a group of urothelial carcinomas versus normal tissues along with clinicopathological factors. Methods This retrospective study included histopathological reports and archival blocks and slides of all patients with urinary bladder cancer treated at King Abdulaziz University Hospital (Jeddah, Saudi Arabia). An anti-galectin-3 monoclonal antibody was used for immunohistochemical staining of tissue microarray slides comprising 128 cases of urothelium carcinoma and 24 specimens of normal bladder mucosa. Results Galectin-3 was downregulated during transformation, with positive expression found in 50 (39%) urinary bladder neoplasms, of which 33 (66%) showed weak immunostaining. All positively-stained malignant tumor and normal bladder mucosa samples showed cytoplasmic staining; a few samples also showed nuclear staining. No correlation was noted between galectin-3 and histotype, grade, stage, muscularis propria invasion, lymph node invasion, vascular invasion, or metastasis. A Cox proportional hazards model and Kaplan–Meier survival curves did not show differences in survival on the basis of galectin-3 expression. Conclusion Galectin-3 is down-regulated in bladder cancer but is not a helpful marker for the diagnosis or prognosis of urinary bladder cancer.